Formulasi Kebijakan Concreto in Abstracto UU ITE - Kurniawan, Efendik; Romadhon, Ahmad Heru; Kusumawardani, Indri Ayu; Zakaria, Zakaria; Rudi Iswono, Akhmad (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 9 No 1 (2020), 2020)
The focus of this research study aims to reaffirm the contents of article 45 paragraph (5) of the ITE Law related to complain offenses which are considered confusing in providing clear definitions and obscurity of legal certainty which can hinder the law enforcement process for justice seekers if there is a dispute in cyberspace. This type of research is normative legal research, descriptive using deductive reasoning. From the results of the discussion, this study shows that the complaint offense listed in the ITE Law which is abstract in nature is blurred if the complaint does not have a more concrete explanation of the meaning of the complaint. So that the Judicial Review needs to review the contents of the article. Policy formulation UU ITE No. 11 of 2008 concerning Information and Electronic Transactions which was last amended by Act No. 19 of 2016 specifically with the interaction of social change and changes in law today address alignments on the one hand in the interests of a group. Fokus dalam studi penelitian ini bertujuan untuk menegaskan kembali isi pasal 45 ayat (5) UU ITE terkait dengan delik aduan yang dirasa membingungkan dalam memberikan definisi yang jelas serta terkaburnya sebuah kepastian hukum yang dapat menghambat proses penegakkan keadilan hokum bagi pencari keadilan apabila ada sengketa di ruang cyber space. Tipe Penelitian ini adalah penelitian hukum normatif, deskriptif dengan mengunakan penalaran deduktif. Dari hasil pembahasan penelitian ini menunjukkan bahwa delik aduan yang tercantum dalam UU ITE yang bersifat abstrak menjadi kabur apabila delik aduan ini tidak mempunyai penjelasan yang lebih konkrit dari arti delik aduan tersebut. Sehingga dirasa perlu Judicial Review mengkaji lagi muatan pasal tersebut. Formulasi kebijakan UU ITE No. 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik yang terakhir diubah dengan Undang-Undang Nomor 19 Tahun 2016 khususnya dengan interaksi perubahan sosial dan perubahan hukum dewasa ini menujukan keberpihakan pada satu sisi dalam kepentingan suatu golongan.